Design and Manufacturing of Axial Flux Permanent Magnet Machines for Electric Vehicle Applications - Abdelli Abdenour; Gilson Adrien; Godefroy Emmanuel; Zito Gianluca (EPJ Web of Conferences)
This paper deals with the design and prototype of an open slot 18-slot/12-pole axial flux permanent magnet (AFPM) machine that meet typical electric vehicle requirements. Multiphysics design is conducted to consider mechanical and thermal constraints in the design stage. The electromagnetic design is based on combination of the 2D and 3D FEA approaches. The rotor losses reduction is performed by magnet segmentation and optimization of the rotor disc. The designed machine is manufactured and tested on the test bench. The experimental results are compared with the simulation results. The impact of the manufacturing process on performance, especially iron losses is investigated.